The effect of cash transfers on mental health: New evidence from South Africa - Julius Ohrnberger; Eleonora Fichera; Matt Sutton; Laura Anselmi (University of Bath, Centre for Development Studies (CDS), 2019)
Mental health and poverty are strongly interlinked. There is a gap in the literature on the effects of poverty alleviation programmes on mental health. We aim to fill this gap by studying the effect of an exogenous income shock generated by the Child Support Grant, South Africa's largest Unconditional Cash Transfer (UCT) programme, on mental health. We use biennial data on 10,925 individuals from the National Income Dynamics Study between 2008 and 2014. We exploit the programme's eligibility criteria to estimate instrumental variable Fixed Effects models. We find that receiving the Child Support Grant improves adult mental health by 0.822 points (on a 0-30 scale), 4.1% of the sample mean. Our findings show that UCT programmes have strong mental health benefits for the poor adult population.
Keywords: 330; Öffentliche Sozialleistungen; Psychische Störung; Südafrika